PENGARUH ETIKA, SANKSI PAJAK, MODERNISASI SISTEM, DAN TRANSPARANSI PAJAK TERHADAP KEPATUHAN PAJAK - Afuan Fajrian Putra (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2017)
This study aims to examine the factors that influence taxpayer compliance in paying taxes. The variables used inthis study include ethics, tax penalties, the modernization of the system, tax transparency and tested its effect on taxcompliance in paying taxes. This research will examine these factors either simultaneously or partially. The populationused in this research are lecturers of all faculty at private university in Yogyakarta. The number of respondents in thisresearch is 86 people, by using formula slovin and the data collecting technique is by questionnaire. The data analysismethod is by multiple regression with the help of statistical software SPSS version 16. The results of this researchindicate that the ethical factors, tax penalties, modernization of the system, and tax transparency simultaneouslysignificant effect on tax compliance in paying taxes While partially, tax penalty, modernizing the system, and thetransparency of the tax are doesn’t positive effect to tax compliance in paying taxes and just ethical factor is positiveeffect to tax compliance in paying taxes.Keywords: Ethics, Tax Penalties, Modernization the System, Tax Transparency, Tax Compliance